Outcome of Pediatric Neuroblastoma at the Children’s Hospital and Institute of Child Health, Lahore - Safwan Ahmad, Muhammad Shafiq, Mahwish Faizan, Huma Zafar, Shazia Riaz, Sadia Anwar, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To demonstrate outcome of pediatric neuroblastoma at The Children’s Hospital and Institute of Child Health, Lahore. Study design: Descriptive observational study Place and duration: The study was conducted in Pediatric Hematology Oncology department, The Children’s Hospital and the Institute of Child Health, Lahore in twelve months from March 2020 to February 2021. Methodology: Study was conducted on total of 60 patients of diagnosed neuroblastoma. Main variables of study were age, parent’s education, socioeconomic status, traveling distance, LTS, and INSS stage, metastatic sites, tumor size and outcome. SPSS version 23.1 was used for data analysis. Test of significance was applied taking p value ≤0.05 as significant value. Results: Regarding histopathology, fifty eight 96% patients had neuroblastoma while 4% patients had ganglioneuroblastoma. Life threatening symptoms were present in 85% patients. Most common primary sites were suprarenal 45%, retroperitoneum 25%, pre/paravertebral 11%, posterior mediastinal 11%, others 6%. Metastasis were present in 40% patients at diagnosis and most common metastatic sites were bone marrow 21%, bone 8% and both 10%. Six(10%) patients with stage 2 showed complete remission ,2(3%) partial remission, 2(3%) patients with stage 3 achieved complete remission ,19(34%) partial remission, 4(7%) patients with stage3 expired, 18(30%) patients with stage 4 were put on palliation initially, 2(3%) patients with stage 4S showed complete remission. Conclusion: The survival outcomes of children with neuroblastoma who were treated at the children hospital lahore between march-2020 and fab-2021are compareable to those in developed and developing countries. A high level of suspicion for neuroblastoma is necessary, especially in children under five years of age with an abdominal mass. This can only be ensured through proper education of health care providers about this aggressive childhood malignancy. Advanced disease presentation is common, high-risk neuroblastoma is considered challenging and has one of the least favourable outcomes among cancers. Late diagnosis due to cultural and socioeconomic barriers and lack of care at primary care level and poor referral to oncology units owing to deficient health care system are still considered the major contributory factors for poor outcome. However, newer treatment strategies are mandated to improve outcomes in pediatric patients who are at high-risk and display relapse. Moreover, multidisciplinary approach with the establishment of infrastructure is the need of time to provide integrated care. Keywords: Neuroblastoma, Outcome, Management, Children